Leptogenesis in Supersymmetric Economical 3-3-1 Model
We study a leptogenesis scenario in which the heavy Majorana neutrinos are produced non-thermally in inflaton decays in the supersymmetric economical \(SU(3)_CSU(3)_L U(1)_X\) model with inflationary scenario. The lepton-number violating interactions among the inflaton and right-handed neutrinos appear at the one-loop level, and this is a reason for non-thermal leptogenesis scenario. The bound followed from the gravitino abundance and the cosmological constraint on neutrino mass/the neutrino oscillation data is: \(m_ u 3 0.05δ_eff \) eV. By taking the reheating temperature as low as \(T_R= 10^6\) GeV, we get a limit on the ratio of masses of the light heavies neutrino to those of the inflaton to be: \(M_R1 M_φ = 0.87\)., number=4, journal=Communications in Physics, author=Huong, Do Thi and Long, Hoang Ngoc and Thuy, Nguyen Thi, year=2011, month=Dec., pages=295